The Spirit of St. Louis [videorecording (DVD)] - Lederer, Charles, 1910-1976 (Warner Home Video, 2006)
Biography of Charles Lindbergh from his days of precarious mail runs in aviation's infancy to his design of a small transatlantic plane and the vicissitudes of its takeoff and epochal flight from New York to Paris in 1927.